A non standar approach to derivatives pricing (2011)
Acknowledgements. Goal Of This Memoire. Role Of The Rating Agencies In The Subprime Crisis. Behavior Of Returns And Descriptive Statistics. About The Options Market. Option Behavior. Other Approach To Derivative Pricing When Financial Assest Do Not Follow Black. Final Comments And Conclusions. Appendix A. Bibliography.